A Stepwise Approach for the Management of Poisoning with Extracorporeal Treatments. Issue 4 (3rd April 2014) - Ghannoum, Marc; Roberts, Darren M.; Hoffman, Robert S.; Ouellet, Georges; Roy, Louise; Decker, Brian Scott; Bouchard, Josée
Abstract The use of an extracorporeal treatment (ECTR) in a poisoned patient may be life‐saving in a limited number of scenarios. The decision‐processes surrounding the use of ECTR in poisoning is complex: most nephrologists are not trained to assess a poisoned patient while clinical toxicologists rarely prescribe ECTRs. Deciding on which ECTR is most appropriate for a poison requires a good understanding of the poison's physicochemical and pharmacokinetic properties. Further, a detailed understanding of the capabilities and limitations of the different ECTRs can be useful to select the most appropriate ECTR for a given clinical situation. This manuscript provides a stepwise approach to assess the usefulness of ECTRs in poisoning.